Second malignancy in young early-stage breast cancer patients with modern radiotherapy: A long-term population-based study (A STROBE-compliant study). Issue 17 (April 2018) - Xie, Liyi; Lin, Chen; Zhang, Huan; Bao, Xuhui
Abstract : Abstract: Second cancer is a leading cause of death in long-term survivors of younger early-stage breast cancer patients. To date, relationship of age, receipt of radiotherapy (RT), and estimated doses received by target organs have not yet been well elucidated. Using Surveillance, Epidemiology, and End Results database, patients aged 20 to 44, diagnosed with a first primary staging I–IIIA ipsilateral breast invasive ductal carcinoma, underwent surgery during 1988 to 2009 were identified, and those with a second malignancy at ≥1-year follow-up were analyzed to calculate cumulative incidences (CIs) of second malignancy in whole group and each subgroup. Subgroups were dichotomized by surgery type, axillary dissection, and axillary lymph node status. With a median follow-up of 11.8 years, 22, 628 women including 1495 patients (6.6%) developing second malignancies (3.7% contralateral breast cancer, 2.9% non-breast second malignancies, and 0.7% high-dose site second malignancies) were identified. Three-dimensional coordinate systems with age at primary diagnosis, time after primary breast cancer diagnosis, and CI of second malignancy as 3 axes, for endpoints including all second malignancy, second primary contralateral breast cancer, and non-breast second malignancy were presented, along with the risk in RT and non-RT groups in overall group and subgroups. Five-, 10-, 15-, and 20-year all second malignancy-free survivals in RT and non-RT groups were 89.5% versus 85.4%, 80.1% versus 75.0%, 72.9% versus 67.9%, and 65.6% versus 61.8% ( P   <  .0001). From the large national dataset, a broad visualized overview of second malignancy risk, including second contralateral breast cancer and non-breast second cancer, suggests generally beneficial therapeutic ratio for radiotherapy in young women with early-stage breast cancer. Abstract : Supplemental Digital Content is available in the text